Empowering learning motivation and experience through cross-age tutoring community service project: Khind education hub to community / Noriah Ismail ... [et al.] - Ismail, Noriah; Soo, Carolyn Kum Yoke; Ahmad, Haryati; Ratan Singh, Deepak Singh; Wan Mohd, Wan Nor Hafidzah; Arbin, Norazam; Elias, Suhaidi; Mohd Ariff Albakr, Intan Safinas (UiTM Cawangan Johor, 2019)
This study investigates the perception of ninety primary school students from Sekolah Kebangsaan Kampung Tengah, Segamat, Johor (SK Kampung Tengah) who were involved in a cross-age tutoring community service EDU HUB Project sponsored by KHIND STARFISH Foundation and organized by University Teknologi MARA (UiTM) Cawangan Johor, Malaysia. The project also involved 30 UiTM Cawangan Johor students who acted as the tutors, and six lecturers who were the advisors for the project. The project was carried out for eight weeks in which the Standard Four and Five students from SK Kampung Tengah were provided with special learning modules which focused on providing learning tips and motivation particularly in learning the English Language, Bahasa Melayu, Mathematics and Science. Two sets of questionnaires were deployed among the tutees prior to and after the project was conducted to analyse their perception of the project and the impact it has made on students’ learning confidence and experience. The findings revealed that the tutees enjoyed being involved in the project as it enhances their confidence, learning interest as well as motivation.